Gambaran Kepuasan Pasien terhadap Pelayanan di IGD Rumah Sakit Ken Saras - Mei Melani; Setyoningrum, Umi (Indonesian Journal of Nursing Research (IJNR), 2024)
The Emergency Room (IGD) is one of the busiest installations in hospitals. The Emergency Room (IGD) must have high quality services so that it can meet good service quality. The quality of hospital services, one of which can be seen from patient satisfaction. Find out the description of patient satisfaction with services at the emergency room at Ken Saras Hospital .The research method was a total sampling quantitative study with a descriptive analytical design. The population used was all emergency room patients, with a sample size of 100 patients. The data collection tool uses a service satisfaction questionnaire in the emergency room. Data analysis uses simple univariate analysis.  Patient satisfaction with the services at the emergency room at Ken Saras Hospital, most of them were satisfied with the services at the emergency room, 98 respondents (98%) and 2% of respondents felt dissatisfied, where in the empathy dimension, the majority felt satisfied, 57 respondents (57%). the tangibles dimension was mostly satisfied with 70 respondents (70%), the responsiveness dimension was mostly satisfied with 54 respondents (54%), the reliability dimension was mostly satisfied with 62 respondents (62%), the assurance dimension was mostly satisfied with 58 respondents (58%). It is hoped that nurses will provide maximum service to all patients without distinguishing between race, ethnicity, economics and social status.   Abstrak Instalasi gawat darurat (IGD) menjadi salah satu instalasi di rumah sakit yang paling sibuk. Instalasi Gawat Darurat (IGD) harus mempunyai pelayanan dengan berkualitas tinggi sehingga dapat memenuhi mutu pelayanan yang baik. Kualitas pelayanan rumah sakit, salah satunya dapat dilihat dari kepuasan pasien. Mengetahui gambaran kepuasan pasien terhadap pelayanan di IGD Rumah Sakit Ken Saras. Metode penelitian studi kuantitatif dengan desain deskriptif analitik.Tehnik sampling total sampling, dengan jumlah sampel 100 pasien. Alat pengumpulan data menggunakan keusioner kepuasan pelayanan di IGD. Analisa data menggunakan analisa univariat sederhana. Kepuasan pasien terhadap pelayanan di IGD RS Ken Saras sebagian besar merasa puas dalam pelayanan di IGD sebanyak 100 responden (100%) ,dimana pada dimensi empati sebagian besar merasa puas sebanyak 100 responden (100%). dimensi tangibles sebagian besar merasa puas sebanyak 100 responden (100%), dimensi responsiveness sebagian besar merasa puas sebanyak 100 responden (100%), dimensi reliability sebagian besar merasa puas sebanyak 84 responden (84%), dimensi assurance sebagian besar merasa puas sebanyak 75 responden (75%). Diharapkan perawat memberikan pelayanan secara maksimal pada seluruh pasien tanpa membedakan ras, suku, ekonomi dan sosial.